Profil Histokimia dan Analisis In Silico Senyawa Metabolit Sekunder pada Daun Zaitun (Olea europaea L.) - Maghfiroh, Lailatul; Rahayu, Tintrim; Hayati, Ari (FMIPA UNISMA, 2018)
Olive (Olea europaea L.) is a plant that is native of the Mediterranean region which was also able to grow in Indonesia. The plants contain secondary metabolite that will be useful for a survival of a certain species. One of the tests to know a compound of the secondary metabolite on the leaves of zaitun is the histochemical analysis. The knowledge about secondary metabolite containing on a tissue of cell can be done the continued testing for ensure secondary metabolite profile of the compound in form of 3D molecular structure that is using in silico analysis. The research aimed to know the histochemical profile and structure of 3D molecular secondary metabolite of olive leaves. The method was used descriptive-qualitative and the research was done two stages; histochemical testing and was continued with visualization of the chemical structure by ‘in silico’ method in form of chemical structure 3D image. The result showed that histochemical analysis at five these secondary metabolites contained in olive leaves; the terpenoids, an alkaloid, phenolic, lipophilic, and flavonoid. While the tannin compound undetectable. All these secondary metabolite containing in olive leaves can be seen in form of 3D structure.Keywords: Olive (Olea europaea L.), secondary metabolites, histochemical, In silicoABSTRAKZaitun (Olea europaea L.) merupakan tanaman yang berasal dari daerah Mediterania yang juga dapat tumbuh di Indonesia. Tanaman zaitun mengandung metabolit sekunder yang bermanfaat untuk pertahanan hidup suatu species tertentu. Salah satu pengujian untuk mengetahui senyawa metabolit sekunder pada daun zaitun adalah dengan analisis histokimia. Pengetahuan tentang kandungan metabolit pada suatu jaringan sel dapat dilakukan pengujian lanjut untuk memastikan profil senyawa metabolit sekunder tanaman dalam bentuk struktur 3D molekular, yaitu menggunakan analisis In silico. Penelitian bertujuan untuk mengetahui profil histokimia dan struktur molekuler 3D metabolit sekunder daun zaitun. Metode penelitian yang digunakan adalah deskriptif kualitatif dan penelitian ini dilakukan dengan 2 tahapan; uji histokimia dan dilanjutkan dengan visualisasi struktur kimia metode in silico berupa struktur kimia gambar 3D. Hasil penelitian menunjukkan bahwa analisis histokimia pada lima metabolit sekunder terkandung pada daun zaitun yaitu terpenoid, alkaloid, fenolik, lipofil, dan flavonoid. Sedangkan senyawa tannin tidak terdeteksi. Semua senyawa metabolit sekunder yang terkandung pada daun zaitun dapat dilihat dalam bentuk struktur 3D.Kata kunci: Zaitun (Olea europaea L.), Metabolit sekunder, Histokimia, In silico